Valvular Regurgitation in a Biventricular Mock Circulatory Loop. Issue 6 (August 2019) - Shehab, Sajad; Allida, Sabine M.; Newton, Phillip J.; Robson, Desiree; Macdonald, Peter S.; Davidson, Patricia M.; Jansz, Paul C.; Hayward, Christopher S.
Abstract : Aortic regurgitation (AR), mitral regurgitation (MR), and tricuspid regurgitation (TR) after continuous-flow left ventricular assist device (LVAD) are common and may increase with prolonged LVAD support. The aim of this study was to simulate severe valvular regurgitation (AR, MR, and TR) within a 4-elemental pulsatile mock circulatory loop (MCL) and observe their impact on isolated LVAD and biventricular assist device (BiVAD) with HeartWare HVAD. Aortic regurgitation, MR, and TR were achieved via the removal of one leaflet from bileaflet mechanical valve from the appropriate valves of the left or right ventricles. The impact of alteration of LVAD pump speed (LVAD 2200–4000 RPM, right ventricular assist device [RVAD] 2400 RPM) and altered LVAD preload (10–25 mm Hg) was assessed. With each of the regurgitant valve lesions, there was a decrease in isolated LVAD pump flow pulsatility. Isolated LVAD provided sufficient support in the setting of severe MR or TR compared with control, and flows were enhanced with BiVAD support. In severe AR, there was no benefit of BiVAD support over isolated LVAD, and actual loop flows remained low. High LVAD flows combined with low RVAD flows and dampened aortic pressures are good indicators of AR. The 4-elemental MCL successfully simulated several control and abnormal valvular conditions using various pump speeds. Current findings are consistent with conservative management of MR and TR in the setting of mechanical support, but emphasize the importance of the correction of AR. Abstract : Supplemental Digital Content is available in the text.